The emperors' needles : Egyptian obelisks and Rome - Sorek, Susan (Liverpool University Press, 2014)
Obelisks, originally associated with the sun cult, had their heyday between 2000 and 1500 bc, when they adorned the Nile's banks and proclaimed the splendour of the pharaohs. Today, only 27 Egyptian obelisks remain standing and they are scattered in various locations throughout the world. Rome, with 13, boasts more than anywhere else, including Egypt itself. This book examines the interest shown in the obelisks by the Roman emperors; it discusses each obelisk in detail, and traces individual histories and anecdotes concerning their journeys from Egypt